ANALISIS FAKTOR- FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2017 - Nisabella Nurulia Sakinah, 15.05.52.0340; Wahyu Widati, Lisyorini (Students' Journal of Accounting and Banking, 2019)
This research aims to examine the effect of profitability, sales growth, , firm size, asset structure, liquidity, and business risk to capital structure at manufacturing companies listed on the Indonesian Stock Exchange (Bursa Efek Indonesia) in 2014-2017.The population in this research are Manufacturing Companies listed on the Indonesia Stock Exchange (Bursa Efek Indonesia). Sampling method using purposive sampling in 2014 until 2017 and obtained as many as 329 companies.The results of this research indicate that firm size, asset structure, and liquidity have a positive significant on Capital Structure while profitability, sales growth, business risk have negative effect on Capital Structure.